Examination of an intervention to enhance relationship satisfaction after brain injury: A feasibility study. (2nd July 2016) - Backhaus, Samantha; Neumann, Dawn; Parrot, Devan; Hammond, Flora M.; Brownson, Claire; Malec, James
Abstract: Background : Brain injury (BI) can adversely affect marriage satisfaction, which can impact rehabilitation outcomes. The objectives of this study were to (1) examine the feasibility of providing a group intervention to individuals with BI and (2) examine if improvements occur in relationship satisfaction and communication following participation. Methods : Nine individuals with BI and their partner participated in a 16-week group intervention targeting relationship skills training. Feedback and satisfaction questionnaires were created to assess feasibility and a pre- and post-test design was used to measure relationship satisfaction and communication. Results : Couples reported high satisfaction with the intervention and workbook and would recommend this intervention to other couples who experience BI. The majority reported satisfaction with the length of treatment, although some felt it was too long. Three couples dropped from the study due to severe cognitive deficits or relationship distress. Couples reported significantly improved satisfaction and quality of relationship and reduced negative communication following the intervention. Conclusions : This intervention may incorporate an appropriate framework for helping couples enhance relationship satisfaction after BI. Given the feasibility and potential for benefit, the hypothesized efficacy of the intervention deserves testing through rigorous research methods, as focusing on improving relationships after a BI could potentially optimize rehabilitation outcomes. Abbreviations : TBI, Traumatic Brain Injury; BI, Brain Injury; CBT, Cognitive-Behavioural Therapy; DBT, Dialectical-Behavioural Therapy